Safety of primary anastomosis following emergency left sided colorectal resection: an international, multi‐centre prospective audit. (25th September 2018) - ,
Abstract: Introduction: Some evidence suggests that primary anastomosis following left sided colorectal resection in the emergency setting may be safe in selected patients, and confer favourable outcomes to permanent enterostomy. The aim of this study was to compare the major postoperative complication rate in patients undergoing end stoma vs primary anastomosis following emergency left sided colorectal resection. Methods: A pre‐planned analysis of the European Society of Coloproctology 2017 audit. Adult patients (> 16 years) who underwent emergency (unplanned, within 24 h of hospital admission) left sided colonic or rectal resection were included. The primary endpoint was the 30‐day major complication rate (Clavien‐Dindo grade 3 to 5). Results: From 591 patients, 455 (77%) received an end stoma, 103 a primary anastomosis (17%) and 33 primary anastomosis with defunctioning stoma (6%). In multivariable models, anastomosis was associated with a similar major complication rate to end stoma (adjusted odds ratio for end stoma 1.52, 95%CI 0.83–2.79, P  = 0.173). Although a defunctioning stoma was not associated with reduced anastomotic leak (12% defunctioned [4/33] vs 13% not defunctioned [13/97], adjusted odds ratio 2.19, 95%CI 0.43–11.02, P  = 0.343), it was associated with less severe complications (75% [3/4] with defunctioning stoma, 86.7% anastomosis only [13/15]), a lower mortality rate (0% [0/4] vs 20% [3/15]), and fewer reoperations (50% [2/4] vs 73% [11/15]) when a leak did occur. Conclusions: Primary anastomosis in selected patients appears safe after left sided emergency colorectal resection. A defunctioning stoma might mitigate against risk of subsequent complications.